Digital Dependency and Security Risk: Investigating the Connections Between Fear of Missing Out, Problematic Social Media Use, and Vulnerability Perceptions - Tourjana Islam Supti (22466692) (2025)
This study aims to investigate the connections between fear of missing out (FoMO), problematic social media use (PSMU), and perceptions of vulnerability, comparing these dynamics across UK and Arab samples. We explore whether these cyber behaviors are driven by inherent traits or influenced by personal intentions of usage and perceptions of risk. This will help focus countermeasures, such as prioritizing whether to adapt the design to personal factors or improve risk perception. Data were collected through a cross-sectional survey design with 642 participants, 314 from the UK and 328 from the Arab region. The study measured how FoMO and PSMU, including demographic factors, age, and gender, influence individuals’ susceptibility to cyber threats, focusing on three key questions: the Likelihood of being targeted by a scam, the Likelihood of a successful scam, and the Encounter of a scam. The results reveal significant associations between FoMO, PSMU, and perceptions of vulnerability, with notable cultural differences. In the UK sample, FoMO and PSMU were strong predictors of the Likelihood of being targeted by a scam, and PSMU is the predictor of the Encounter of a scam, suggesting that higher level FoMO and PSMU are linked to greater online vulnerability. However, in the Arab sample, while FoMO was positively associated with the Likelihood of a successful scam, PSMU did not significantly predict the Likelihood of a successful scam. This discrepancy indicates that cultural or contextual factors may influence the relationship between FoMO, PSMU, and vulnerability perceptions differently across regions. The findings underscore the importance of considering cultural context when addressing digital behavior and cybersecurity vulnerabilities. Future research should explore how varying forms of social media engagement and cultural factors impact these relationships to develop more effective, culturally tailored interventions. Other Information Published in: Journal of Technology in Behavioral Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41347-025-00515-0